Review on InSAR based displacement monitoring of Indian Himalayas: issues, challenges and possible advanced alternatives. Issue 3 (4th March 2017) - Bhattacharya, Atanu; Mukherjee, Kriti
Abstract: Natural and man-made disasters like earthquakes, landslides, avalanches, unplanned mining are some of the most serious factors responsible for earth surface displacement. These incidences can be harmful for the society due to loss of life and also threatful for future urban development. Therefore, continuous monitoring of disasters in terms of displacements is of fundamental importance in a modern well-organized society to understand its effects on the social and economic fabric. Availability of SAR data has been proved to be an excellent source for estimation of surface displacements with high accuracies. However, in India, SAR interferometry-related displacement measurement has still not gained appreciable momentum. More rigorous research needs to be carried out for the efficient use of this new generation technique. This review article is an attempt to discuss the issues related to SAR-based displacement studies so far conducted on Indian Himalayan region and possible advanced alternatives.